Understanding Different Geographies - Kriz, Karel; Cartwright, William; Kinberger, Michaela; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book collects revised versions of papers first delivered at the “Understanding Different Geographies Symposium” held in Puchberg am Schneeberg, Austria in 2011.  The Symposium focussed on “Communicating Meaning with [Geo]Graphic Artefacts”.  The general topics of the chapters cover: - Exploring geographic knowledge - Maps in exhibition spaces - Information and exhibition design with (geo)graphic artefacts - Extracting meaning from visualisations of different geographies - Deconstructing maps of information - and other spaces.
From the Contents: Maps and Design -- Cartography utilizing Geo-Communication -- Understanding different geographies: the case for drawings and sketches -- Artefacts and geospaces -- Understanding Artefacts through Geographies – Perceiving Geographies through Artefacts -- Harriet Edquist and Lisa Byrne: Understanding Place -- When countries become gods – some thoughts on the geospatial aspect of deities and demons in India -- Exhibitions and Geospace -- Potential Information Gains for Exhibition Makers and their audience in Mapping the Movement of Objects -- Representations and Geospace -- The Geography of Uncertainty: Outcomes Spaces and Uncertainty Visualization.
Keywords: Geographical information systems; Geographical Information Systems/Cartography.